Comparison of different methodologies for estimating gold thickness in multilayer samples using XRF spectra. (January 2023) - Scialla, Elvira; Brocchieri, Jessica; Sabbarese, Carlo
Abstract: A detailed comparison of methodologies for assessing gold leaf thickness in multilayer samples using the XRF technique was performed. Standard three-layer samples and six methods of analysis were used: two-line ratio of one or two elements, de Boer's analytical procedure, multivariate PLS analysis and percentage concentration of elements in the layers. The accuracy of each method and the consistency among the results of the methods emerged. The PLS method and the analytical approach might be preferred because they are faster. Highlights: The novelty of this study is the comparison of six procedures for calculating a thickness of gold. Standard samples with three layers were made and the thickness of the core layer was determined. The procedures are based on the analysis of XRF spectra, on analytical calculations and on simulation. The study highlights the characteristics and accuracy of each procedure. The results found are useful for museum conservators and restorers, as well as for research.